2022
DOI: 10.1002/ijc.34137
|View full text |Cite
|
Sign up to set email alerts
|

PSC subtyping based on TTF‐1 and p40 expression reveals distinct molecular characteristics and therapeutic strategies

Abstract: Pulmonary sarcomatoid carcinoma (PSC) is a unique form of poorly differentiated nonsmall cell lung cancer (NSCLC) and is notorious for its highly malignant nature and dismal prognosis. To introduce effective treatment for PSC patients, precise subtyping of PSC is demanding. In our study, TTF-1 and P40 immunohistochemistry (IHC) staining were applied to 56 PSC patients with multiomics data. According to IHC results, we categorized these patients into three subgroups and profiled their molecular contexture using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…TTF-1 is often expressed unexpectedly in a large number of cases of PSC. A multi-omics study ( 15 ) based on TTF-1 and P40 immunohistochemistry (IHC) established a new PSC typing method that was simpler and more economical than genotyping. they divided PSC patients into three subtypes (TTF-1 positive group, P40 positive group, and double negative group).…”
Section: Discussionmentioning
confidence: 99%
“…TTF-1 is often expressed unexpectedly in a large number of cases of PSC. A multi-omics study ( 15 ) based on TTF-1 and P40 immunohistochemistry (IHC) established a new PSC typing method that was simpler and more economical than genotyping. they divided PSC patients into three subtypes (TTF-1 positive group, P40 positive group, and double negative group).…”
Section: Discussionmentioning
confidence: 99%
“…EGFR mutations were found in 5.0%–22.6% of patients with PSC. 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 Liu et al. 83 reckoned EGFR -sensitizing mutations as one of the trunk mutations in PSC despite high intratumor heterogeneity (ITH).…”
Section: Efficacy Of Fda-approved Targeted Therapiesmentioning
confidence: 99%
“…METex14 skipping mutations were detected in 2.0%–31.8% of PSC, which was more frequent than that of other NSCLC subtypes. 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 89 , 90 , 91 Several retrospective studies of patients with METex14 -positive lung cancer, including PSC patients, reported a partial response to first-line crizotinib, a multitargeted TKI covering MET. 92 , 93 In addition, an open-label, phase 2 clinical trial of tepotinib, a highly selective MET TKI, enrolled two PSC patients out of 152 in total, with an ORR of 46% and a median duration of response of 11.1 months.…”
Section: Efficacy Of Fda-approved Targeted Therapiesmentioning
confidence: 99%
See 1 more Smart Citation